Heart Rate variability in an elite female road cyclist: A comparison of techniques - Wisbey, B.; Montgomery, P.; Martin, D.; McDonald, W. (Australian Conference of Science and Medicine in Sport and Third National Sports Injury Prevention Conference: 2003. Tackling the barriers of performance and participation, 2003)
Heart Rate Variability (HRV) and training load were monitored daily in one elite female road cyclist (22 yr, 55 kg, 66 ml.kg-1.min-1 VO2max) for 28 days during the 2003 cycling season. HRV data were collected using a commercially available HR monitor (S810, Polar Electro) during a daily orthostatic challenge (ORTHO - 3min supine, 2min standing). HRV was assessed with Nevrokard HRV software (Medistar, Slovenia) using both a time-based and a fast Fourier transform (FFT) analysis to quantify: 1) low frequency signal (LF), 2) high frequency signal (HF), 3)LF/HF ratio, 4) percentage of R-R intervals with a change >50ms (pNN50), and 5) standard deviation of the X and Y axis of the Poincare plot (SD1 and SD2). Training load was quantified using a modified HR TRIMP calculation. Coefficient of variation (%CV) was used as an index of daily variation and was ~60% for training (TRIMP) and LH/HF. %CV was lower (~30%) for LF, HF, SD1, and pNN50, and much lower (~13%) for SD2. As expected, LF/HF strongly correlated to LF(r=0.95) and HF(r=-0.95). The correlations were moderate between LF/HF and SD1(r=-0.62) and pNN50(r=-0.62) suggesting that these parameters reflect unique aspects of autonomic tone. Interestingly, HRV variables did not correlate with TRIMPS when examined using daily or a 3d rolling average. In summary, FFT and time-based HRV parameters are unique. HRV does appear to be influenced by training load but does not simply reflect changes in daily training suggesting that this HR parameter may provide insight into a unique aspect of exercise-induced fatigue.